PEMBELAJARAN MENGGUNAKAN MEDIA SASTRA TRADISIONAL DALAM MENGEMBANGKAN NILAI PERSONAL ANAK USIA DINI - RASMINI, NI WAYAN (Jurnal Pendidikan Usia Dini, 2017)
The aim of this study was to understand the characteristic of learning plans, learning activities, and learning implications of using traditional literatures as learning media in developing personal values of kindergarten chidren at Cahaya Ananda Kindergarten in Mataram. Personal values purposed in this study were: emotional value, intelegency, imagination, sosial value, ethics, and religious value. Traditional literatures purposed in this study were: mythos, legends, fabels, folklores, folksongs, and wayang stories told generations after generations around children subjected to this study. This study was an ex-post facto descriptive quantitative study. From this study we found that the characteristic of Daily Learning Plans used in subject kindergarten has been appropriate with national Daily Learning Plans now used. Environment oriented prior-to-play learning process was integrated in outside-class initial activities. Teachers have included traditional literatures in learning plans and learning process and have shown to increase children’s personal values. At the end of learning process children have shown increase in: emotional value, intelectuality, imagination, empathy, ethics, and religiousity. Keywords: learning media, traditional literatures, personal values